Known unknowns: how might the persistent herpesvirome shape immunity and aging?. (October 2017) - Nikolich-Zugich, Janko; Goodrum, Felicia; Knox, Kenneth; Smithey, Megan J
Highlights: HSV-1, HSV-2, VZV, EBV and CMV persist widely in humans and play a potential role in human aging. Subclinical herpesvirus reactivations occur throughout the lifespan, and require ongoing immune attention to control these viruses, thus influencing immune aging. Each herpesvirus exhibits a different host cell tropism and viral reservoir, so immune control will require different levels of immune resources, and this may change over the lifespan. Of the five, CMV infection specifically has been associated with numerous "diseases of aging", yet recent results show benefits of CMV infection, highlighting a nuanced interaction between CMV and the aging host. Abstract : The microbial community that colonizes all living organisms is gaining appreciation for its contributions to both physiologic and pathogenic processes. The virome, a subset of the overall microbiome, large and diverse, including viruses that persistently inhabit host cells, endogenous viral elements genomically or epigenomically integrated into cells, and viruses that infect the other (bacterial, protozoan, fungal, and archaeal) microbiome phylla. These viruses live in the organism for its life, and therefore are to be considered part of the aging process experienced by the organism. This review considers the impact of the persistent latent virome on immune aging. Specific attention will be devoted to the role of herpesviruses, and within them, the cytomegalovirus, as the key modulators of immune aging.